HISTORY OF THE CREATION OF MEDICAL SCIENCES IN THE EAST AND THE WEST - Professor Bakayev Najmiddin (Bright Mind Publishing, 2025)
This article discusses the problems and foundations of teaching students the laws of medicine in higher medical education institutions, as well as the creation of psychological theoretical understandings in their practical implementation and development.
Keywords: Use of laws, diseases, hematology, anatomy, physiology.